The feminism and visual culture reader - Jones, Amelia (Routledge, 2010)
Feminism is one of the most important perspectives from which visual culture has been theorized and historicized over the past forty years. Challenging the notion of feminism as a unified discourse, this second edition of The Feminism and Visual Culture Reader assembles a wide array of writings that address art, film, architecture, popular culture, new media and other visual fields from a feminist perspective. The essays, 40% of which are new to the second edition, are informed by the authors’ deep attention to historical, geographical, and disciplinary contexts as well as by cutting edge concerns such as globalization, diasporic cultural shifts, developments in new media technologies, and intersectional identity politics. The Feminism and Visual Culture Reader combines classic texts with six specially commissioned pieces, all by leading feminist critics, historians, theorists, artists, and activists. Articles are grouped into thematic sections, each of which is introduced by the editor. Providing a framework within which to understand the shifts in feminist thinking in visual studies, as well as an overview of major feminist theories of the visual, this reader also explores how issues of race, class, nationality, and sexuality enter into debates about feminism in the field of the visual
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; arts visuels et médiatiques; cours; discipline; discours dominant; fem1000; genre; har4600; identités LGBTQIA2+; interdisciplinarité; intersectionnalité; premier cycle; périodes historiques; racialisation; sexualité; systèmes d'oppressions; thématiques; théories féministes; études culturelles

Femmes artistes du XXe siècle au Québec: œuvres du Muséee national des beaux-arts du Québec - Musée national des beaux-arts du Québec.; Trépanier, Esther (Collection Arts du Québec, 2010)
Cet ouvrage, abondamment illustré d’œuvres tirées de la collection du Musée national des beaux-arts du Québec, constitue un hommage sans précédent à une centaine de femmes qui ont contribué à la vitalité de l’art québécois du XX e siècle. Le premier chapitre, intitulé La conquête d’un espace, 1900-1965 , est consacré aux premières décennies du siècle, alors que le second, L’éclatement des frontières, 1965-2000 , embrasse la période contemporaine. Enfin, une troisième section en forme de dictionnaire présente des notices biographiques sur les 100 artistes retenues. Ce livre est le premier titre de la collection « Arts du Québec », qui veut ouvrir de nouvelles perspectives sur l’art d’ici en explorant l’histoire de l’art québécois dans toute sa diversité, tout en convoquant des dimensions sociologiques, thématiques ou esthétiques inédites.
Keywords: 1900-1999; amériques; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; thématiques